Considering the Question of the interoperability - Sacramento, Eveline R.; Sardo, Susana; Miguel, Ana Flávia; Caixinha, Hélder J. M.; Cortês, Cristina (Páginas a&b: arquivos e bibliotecas, 2022)
This article concerns the path taken during my scientific research related to the construction and management of digital assets for the design, development, and management of databases, within the scope of the INET-md in Portugal. Its general objective is to facilitate the interoperability, Web dissemination, search, and retrieval of the INET-md's digital collections. This investigation aims to reinforce the alliance between the areas of Information Science and Computer Science. From the Information Science, it brings the applications used for organization, management, and publication of digital assets collections on the Web; and from the Computer Science, it brings syntactic concepts (metadata and protocols) to communicate and exchange data and semantic concepts (ontologies and semantic annotations) to describe data. Both types of concepts can promote interoperability between distinct digital repositories and platforms, providing improvements in information search and retrieval activities.